District Liaison Involvement in Partnership Academies - Debra Gustafson; Nancy Kiltz (Educational Considerations, 2016)
The greatest legacy a leader can leave is having developed other leaders…if you want to leave a legacy, invest in people, and encourage those you develop to pass on everything they learn from you to others who will do the same.
Keywords: philosophy; Kansas State University; administrators; Political; District Liaison; collaborative effort; academy; Curriculum